The relationship between collocation competence and writing skills of EFL learners - Mohd Abdi, Bilan; Ariffin, Adlina (Universiti Pendidikan Sultan Idris, 2020)
This paper aims to highlight the importance of collocations in learning English as a foreign language. Learning collocations is deemed crucial for it enables EFL learners to position words in suitable context and use them appropriately. A word may not be correctly utilised or understood unless one is familiar with the immediate context in which the word is used. Furthermore, collocations are regarded as an important factor in communicative competence and in determining learners’ level of proficiency (James, 1998; Nation, 2001). The current study aimed to explore the effects of students’ knowledge of collocation on their writing production. The participants were 20 Djiboutian postgraduate students undergoing their studies in one of the higher learning institutions in Malaysia. Utilising a multiple-choice test consisting of 60 items and a writing test, this study sought to investigate the correlation between lexical collocation knowledge and writing skills of the Djiboutian students. The results from the study revealed a positive correlation between the collocational knowledge and writing production. It was also found that Djiboutian EFL learners did have difficulties in English lexical collocations. These findings corroborated the need for EFL students to learn lexical collocations in order to develop their writing skills. The outcomes of this study provide useful lessons to foreign language learners, teachers, curriculum designers and material developers in the teaching and learning of English as a foreign language.